RESEARCH OF THE TOURISTIC POTENTIAL AT THE BORDERLAND OF THE EU - Supply and demand in the Upper-Tisza Region (PANGEEA, 2025)
The north east part of the Carpathian Basin is a part of the most important transport corridor of EU, furthermore there is a diverse area both from the point of view of natural and social endowments as well. The most important value of the underdeveloped areas from the point of view of economy is its capabilities concerning transport geography and tourism. Here the borders of five countries (of wich 4 are members of EU) meet each other within a very small range which is a serious possibility from the point of view of transport corridor development both in the direction of northeast-south west and north-south. Nevertheless it is also important that transport and logistics should not endanger the unique natural and ethnographical values of the region. Based on the tourism flow we can state that the Hungarian side of the region possesses adequate attractions, however these advantages are not yet successfully utilised. The biggest opportunity of the region is to attract greater number of guests from the neighbouring countries.
Keywords: Borders; Hungary; Ukraine; tourism; destinations; spa; transport; logistics; regional development